A Fill from a Potter’s Dump at Morgantina - Stone, Shelley (Journal of Hellenistic Pottery and Material Culture, 2016)
The excavations at Morgantina in Sicily have now proceeded for 60 years, and items excavated in the first years are even now just being studied. This paper presents a fill excavated in 1956 in the area of Morgantina’s monumental Central Steps in the Agora, an architectural feature which has been interpreted as an Ekklesiasterion. The ceramics were deposited in successive strata at the end of a drain line (fig. 3) that channeled the torrential rainwaters characteristic of central Sicily away from the Steps. The interest of the superimposed fills at the end of the drainline lies in two reasons. First, the date of deposit(s) can be placed in the first third of the 1st century BCE, and the pottery thus dates to the late 2nd or early 1st BCE. This is important because of the paucity of well-dated fills in Sicily from the 2nd century BCE. Even more important is the source of the ceramics, since wasters and multiples of the same shape and size indicate that the fill was brought from a potters’ dump, which must be that of the large Pottery built into the old East Granary at Morgantina, located around thirty meters from the deposit (fig. 1). The Pottery is interesting because it manufactured a full range of household ceramics from around 130 to around 50 BCE, when it was abandoned. This paper will examine first the circumstances of the deposit and its chronology, and then its range of ceramics.